2020
DOI: 10.1002/sia.6753
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐instrument characterization of HiPIMS and DC magnetron sputtered tungsten and copper films

Abstract: Funding information Kurt J. Lesker CompanyIn this work, copper and tungsten were sputtered onto silicon wafers by direct current magnetron sputtering (DCMS) and high-power impulse magnetron sputtering (HiPIMS). The resulting films were characterized by energy dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), atomic force microscopy (AFM), spectroscopic ellipsometry (SE), and X-ray diffraction (XRD). By EDX and XPS, all the sputtered films showed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Sputter-deposited tungsten thin films exhibit two phases, the equilibrium α−W (A2 bcc) and the metastable β−W (A15 cubic) phases. HiPIMS-deposited tungsten films are denser, exhibit smaller grains and better adhesion [13][14][15] in addition to higher hardness, higher Young's modulus values, and smoother surfaces [13,16,17]. This is well demonstrated by Shimizu et al [15] who reported stress-free, unstrained single phase α−W thin films, deposited by applying a synchronized substrate bias to selectively increase the energy of the metal population of the ion bombardment.…”
Section: Introductionmentioning
confidence: 64%
“…Sputter-deposited tungsten thin films exhibit two phases, the equilibrium α−W (A2 bcc) and the metastable β−W (A15 cubic) phases. HiPIMS-deposited tungsten films are denser, exhibit smaller grains and better adhesion [13][14][15] in addition to higher hardness, higher Young's modulus values, and smoother surfaces [13,16,17]. This is well demonstrated by Shimizu et al [15] who reported stress-free, unstrained single phase α−W thin films, deposited by applying a synchronized substrate bias to selectively increase the energy of the metal population of the ion bombardment.…”
Section: Introductionmentioning
confidence: 64%
“…Magnets are often used in this type of sputtering to trap the electrons near the target surface and increase their effective path lengths, which substantially increases their ionization efficiencies. 19,20) Since RF (Radio Frequency) magnetron sputtering has its own difficulty for the requirement of impedance matching of the power supply, and also has low deposition rate. Whereby, this study explored the relatively easier technique of DC magnetron sputtering which does not have the impedance matching problem.…”
Section: Wear and Corrosion Resistance Of Crn Films On Oxynitridingtr...mentioning
confidence: 99%
“…Deposition of tungsten thin films by dcMS and HiPIMS results in textured films that consists of two phases, the equilibrium α-W (A2 bcc) and the metastable β-W (A15 cubic). The HiPIMS-deposited films are denser, have smaller grains and better adhesion [13][14][15]. Furthermore, HiPIMS-deposited tungsten thin films exhibit enhanced properties, including smoother surfaces, higher hardness, and Young's modulus values [13,16,17].…”
Section: Introductionmentioning
confidence: 99%